Creación de contenido en Instagram: ‘Yoga en la U’ - Castañeda Flores, Lorena Ninowska (2021)
Yoga en la U, also Yoga at the University, is a social project deployed on the Instagram social network. In the profile, the publications are their own digital illustrations where a main character, Nina, shows Yogic practices with the purpose of being used to improve the quality of student life taking into account the physical, mental health and academic performance of the student. The Yoga content offered is informative and has a student focus, for example, breathing exercises to improve concentration during study. The work in the creation of a different content was essential to consolidate a new proposal with respect to other Yoga blogs; The graphic and illustrative style, and the communicational tone, were developed in order to present Yoga en la U as an informative, youthful and entertaining space that is characterized by disseminating useful content in a simple language made available to any university student who is interested in learning about an alternative style of living, and maximize performance.